1957
DOI: 10.1039/df9572400133
|View full text |Cite
|
Sign up to set email alerts
|

Ion-solvent interaction. Structural aspects of ion-solvent interaction in aqueous solutions: a suggested picture of water structure

Abstract: In addition to the direct action of the ionic charge on water as a dielectric medium, ions may exert an influence on the equilibrium between the ice-like and non-ice-like forms which are present in room-temperature water. This provides a way of accounting for experimental results in a variety of areas, including entropy, heat capacity, temperature of maximum density, tracer self-difhsion, thermal conductivity, and dielectric relaxation, as well as viscosity and ionic mobility and their temperature coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
664
1
4

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,888 publications
(714 citation statements)
references
References 4 publications
31
664
1
4
Order By: Relevance
“…The molar heat capacity of the liquid at constant atmospheric pressure is also particularly large and is close to twice that of the solid near the normal freezing point and to twice that of the vapor near the normal boiling point [15]. The above-noted expectations are clearly consistent with these experimental findings and with numerous experimental and theoretical observations suggesting that the particulate constituents of liquid water consist largely of labile clusters of molecules, the concentration and average size of which depend on temperature and pressure [15][16][17][18].…”
Section: Thermodynamics Of Liquids and Solidssupporting
confidence: 77%
“…The molar heat capacity of the liquid at constant atmospheric pressure is also particularly large and is close to twice that of the solid near the normal freezing point and to twice that of the vapor near the normal boiling point [15]. The above-noted expectations are clearly consistent with these experimental findings and with numerous experimental and theoretical observations suggesting that the particulate constituents of liquid water consist largely of labile clusters of molecules, the concentration and average size of which depend on temperature and pressure [15][16][17][18].…”
Section: Thermodynamics Of Liquids and Solidssupporting
confidence: 77%
“…13 This energy-based definition of cooperativity has been traditionally used in the discussion of cooperative phenomena in intermolecular H-bonded systems. 14 Other definitions for the cooperativity have been used in the literature 15 because the effects of cooperativity can be manifested in properties other than the energetics. For instance, several groups have shown that a quantitative treatment of cooperativity effects in intermolecular and intramolecular H bonds can be achieved in terms of the relative vibrational frequency shifts undergone by the X-H group involved in the hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Each sp 3 hybridized oxygen atom can form four approximately tetrahedrally disposed hydrogen bonds in liquid water 37 . Similar to water, ethanol can be regarded as having a sp 3 hybridized tetrahedral oxygen 38 .Since the oxygen atom of an ethanol molecule carries one proton and two lone pairs of electrons, it might form three hydrogen bonds with its neighbors -another ethanol molecule or a water molecule 38 .…”
Section: Wettability Of Hydrophilic and Hydrophobic Capillariesmentioning
confidence: 99%